2018
DOI: 10.1186/s40478-018-0567-4
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 activation links tau hyperphosphorylation and Aβ dysmetabolism in Alzheimer’s disease

Abstract: One of the earliest pathological features characterizing Alzheimer’s disease (AD) is the loss of dendritic spines. Among the many factors potentially mediating this loss of neuronal connectivity, the contribution of Rho-GTPases is of particular interest. This family of proteins has been known for years as a key regulator of actin cytoskeleton remodeling. More recent insights have indicated how its complex signaling might be triggered also in pathological conditions. Here, we showed that the Rho-GTPase family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 76 publications
1
50
1
Order By: Relevance
“…Rac1 is increased in plasma samples of AD patients [162] and, in the hippocampus of AD mice, Rac1 was abnormally activated at the early stages of the pathology, even if the total protein levels decreased at full-blown pathology stage. These data suggest that, in an initial stage, Rac1 deregulation might represent a triggering co-factor due to the direct effect on Aβ and tau [162]. Evidence of actin involvement in AD comes from studies of the main neuropathological hallmarks of AD, i.e., neurofibrillary tangles and the senile plaque, and of the additional lesions that are detectable in AD brains, such as the Hirano bodies and the actin rods.…”
Section: Actin Cytoskeleton Pathology In Admentioning
confidence: 94%
See 1 more Smart Citation
“…Rac1 is increased in plasma samples of AD patients [162] and, in the hippocampus of AD mice, Rac1 was abnormally activated at the early stages of the pathology, even if the total protein levels decreased at full-blown pathology stage. These data suggest that, in an initial stage, Rac1 deregulation might represent a triggering co-factor due to the direct effect on Aβ and tau [162]. Evidence of actin involvement in AD comes from studies of the main neuropathological hallmarks of AD, i.e., neurofibrillary tangles and the senile plaque, and of the additional lesions that are detectable in AD brains, such as the Hirano bodies and the actin rods.…”
Section: Actin Cytoskeleton Pathology In Admentioning
confidence: 94%
“…In neuronal cultures exposed to fibrillar Aβ peptide, an increased localization and activity of Rac1/Cdc42 Rho GTPases, promoted by Tiam1, were observed together with a consequent enhancement in actin polymerization [161]. Rac1 is increased in plasma samples of AD patients [162] and, in the hippocampus of AD mice, Rac1 was abnormally activated at the early stages of the pathology, even if the total protein levels decreased at full-blown pathology stage. These data suggest that, in an initial stage, Rac1 deregulation might represent a triggering co-factor due to the direct effect on Aβ and tau [162].…”
Section: Actin Cytoskeleton Pathology In Admentioning
confidence: 98%
“…Rac1 is also involved in another type of AD mice model, the 3xTg-AD. It is shown that Rac1 activity is increased in 6-week-old 3xTg-AD mice (Borin et al, 2018). Moreover, in primary cortical neurons, Rac1 or constitutively active mutant forms of Rac1 constructs led to the creation of pathogenic Aβ fragments and the translocation of SET from the nucleus to the cytoplasm, which also resulted in increased phosphorylation of tau.…”
Section: Rac1 Gtpase In Brain Disordersmentioning
confidence: 98%
“…Regulation of Rac1 is a key determinant of neurologic health and is implicated in several neurologic diseases, including AD [5][6][7][8][9][10][11]. Given the wealth of preclinical evidence and the scarcity of human studies of Rac1 and AD, we sought to evaluate the association between Rac1 inhibitors, thiopurines, and incident AD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 has been implicated in Alzheimer's disease (AD) process [5], leading to increased amyloid precursor protein (APP) processing and stimulated tau hyperphosphorylation [6]. Evidence suggests Rac1 deregulation may be an AD trigger due to its effect on both APP and tau [6]. Furthermore, Rac1 inhibition in vascular endothelial cells could confer neuroprotection through the upregulation of artemin, a neurotrophic factor [7].…”
Section: Introductionmentioning
confidence: 99%